2010
DOI: 10.1210/me.2010-0116
|View full text |Cite
|
Sign up to set email alerts
|

Isoform-Specific Degradation of PR-B by E6-AP Is Critical for Normal Mammary Gland Development

Abstract: E6-associated protein (E6-AP), which was originally identified as an ubiquitin-protein ligase, also functions as a coactivator of estrogen (ER-α) and progesterone (PR) receptors. To investigate the in vivo role of E6-AP in mammary gland development, we generated transgenic mouse lines that either overexpress wild-type (WT) human E6-AP (E6-AP(WT)) or ubiquitin-protein ligase-defective E6-AP (E6-AP(C833S)) in the mammary gland. Here we show that overexpression of E6-AP(WT) results in impaired mammary gland devel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 63 publications
3
22
0
Order By: Relevance
“…Both RU486 and Wnt inhibitors blocked this effect of R5020, indicating that both the genomic action of PRB and the activation of the Wnt pathway were required to decrease the E-cadherin protein. These results are consistent with previous reports that P acting through PRB induces Wnt-1 and Wnt-4 mRNA in YB cells, and loss of Wnt1 blocks soft agar growth of YB T47D cells [32,33]. However, other Wnt proteins may be induced by PS to regulate E-cadherin.…”
Section: Discussionsupporting
confidence: 93%
“…Both RU486 and Wnt inhibitors blocked this effect of R5020, indicating that both the genomic action of PRB and the activation of the Wnt pathway were required to decrease the E-cadherin protein. These results are consistent with previous reports that P acting through PRB induces Wnt-1 and Wnt-4 mRNA in YB cells, and loss of Wnt1 blocks soft agar growth of YB T47D cells [32,33]. However, other Wnt proteins may be induced by PS to regulate E-cadherin.…”
Section: Discussionsupporting
confidence: 93%
“…In fact, BMI1 is essential for normal functional interaction of the PR with E6AP. A previous study has shown that E6AP is involved in human PRB ubiquitination for its timely turnover via the proteasome pathway during mammary gland development (32). In this regard, we observed a comparable expression level of PR proteins upon the loss of Bmi1, pointing toward a disassociation of PR ubiquitination by the BMI1-PR-E6AP complex from the process of PR protein turnover.…”
Section: Animals and Treatments Bmi1supporting
confidence: 72%
“…increased in brain lysates derived from Ube3a-null mice (26)? E6AP was reported to affect nuclear hormone receptor-mediated transcription by E3-independent and E3-dependent mechanisms (41)(42)(43). Furthermore, expression of the human Arc gene is increased by estradiol signaling (44).…”
Section: E6apmentioning
confidence: 99%